Driving factors of e-waste recycling rate in 30 European countries: new evidence using a panel quantile regression of the EKC hypothesis coupled with the STIRPAT model - Bilal Boubellouta; Sigrid Kusch-Brandt (Environment, Development and Sustainability, 2022)
Recycling of e-waste (waste electrical and electronic equipment) represents an important abatement of pressure on the environment, but recycling rates are still low. This study builds on common environmental economics approaches to identify the main driving forces of the e-waste recycling rate. The environmental Kuznets curve hypothesis was applied in the context of the STIRPAT (stochastic impacts by regression on population, affluence and technology) model to analyze data from 30 European countries over the period 2008–2018. Panel quantile regression was conducted to determine the relationship between e-waste recycling rate and economic growth, population, population density, energy intensity, energy efficiency, credit to private sector and e-waste collected. Strong evidence was found that the relationship between economic growth and e-waste recycling rate is an N-shaped curve, i.e., the e-waste recycling rate first increases with economic growth, then decreases in maturing economies and in mature economies starts increasing again as the economy continues to grow. In addition to the economic development stage of a country, e-waste collection was identified as an important determinant of the e-waste recycling rate, regardless of whether the already achieved recycling rate was low, medium or high. In all models, a rise of the collected e-waste quantity was linked to an increase in the recycling rate. Therefore, expanding e-waste collection represents a priority task for policy makers to achieve high e-waste recycling rates. Population, energy intensity and credit to private sector also had an impact and in tendency displayed a negative effect on the e-waste recycling rate; however, the impact of these variables was more relevant for countries with particularly low e-waste recycling rates.
Keywords: 330; E-waste recycling; Environmental abatement; Environmental economics; Environmental Kuznets curve; STIRPAT model; Panel quantile regression